The efficiency of the Warsaw Stock Exchange : the first few years 1991-1996 - Wheeler, Fred P.; Neale, Bill; Kowalski, Tadeusz; Letza, Steve R. (Economics and Business Review, 2002)
This paper reports a test of the changing pricing efficiency of the first stage of development of the Warsaw Stock Exchange (WSE). Emerging stock markets are unlikely to be fully information-efficient, partly due to institutional rigidities which restrict information flows to the market and partly for lack of experienced market participants to rapidly impound new information into security prices. Tests for runs and autocorrelation were conducted for the 1991-1996 trading history of the WSE and also to segmented sub-periods during which different institutional arrangements applied. As the number of trading days per week increased, the general level of efficiency, although low, steadily improved (except for the "bubble" period of 1993-1994). Inefficiencies persist in some stocks, possibly explained by opportunities to conduct off-market, out-of-hours transactions in specific stocks, and the stock exchange authorities' continuing power to suspend trading. (original abstract)